The effects of inpatient exercise therapy on the length of hospital stay in stages I–III colon cancer patients: randomized controlled trial - Ahn, Ki-Yong; Hur, Hyuk; Kim, Dong-Hyun; Min, Jihee; Jeong, Duck Hyoun; Chu, Sang Hui; Lee, Ji Won; Ligibel, Jennifer A.; Meyerhardt, Jeffrey A.; Jones, Lee W.; Jeon, Justin Y.; Kim, Nam Kyu (International journal of colorectal disease, 2013)
Purpose This study aimed to examine the effects of a postsurgical, inpatient exercise program on postoperative recovery in operable colon cancer patients Methods We conducted the randomized controlled trial with two arms: postoperative exercise vs. usual care. Patients with stages I–III colon cancer who underwent colectomy between January and December 2011 from the Colorectal Cancer Clinic, were recruited for the study. Subjects in the intervention group participated in the postoperative inpatient exercise program consisted of twice daily exercise, including stretching, core, balance, and low-intensity resistance exercises. The usual care group was not prescribed a structured exercise program. The primary endpoint was the length of hospital stay. Secondary endpoints were time to flatus, time to first liquid diet, anthropometric measurements, and physical function measurements. Results A total of 31 (86.1 %) patients completed the trial, with adherence to exercise interventions at 84.5 %. The mean length of hospital stay was 7.82 ± 1.07 days in the exercise group compared with 9.86 ± 2.66 days in usual care (mean difference, 2.03 days; 95 % confidence interval (CI), −3.47 to −0.60 days; p = 0.005) in per-protocol analysis. The mean time to flatus was 52.18 ± 21.55 h in the exercise group compared with 71.86 ± 29.2 h in the usual care group (mean difference, 19.69 h; 95 % CI, −38.33 to −1.04 h; p = 0.036). Conclusions Low-to-moderate-intensity postsurgical exercise reduces length of hospital stay and improves bowel motility after colectomy procedure in patients with stages I–III colon cancer.